2012
DOI: 10.1186/1471-230x-12-21
|View full text |Cite
|
Sign up to set email alerts
|

Dome-type carcinoma of the colon; a rare variant of adenocarcinoma resembling a submucosal tumor: a case report

Abstract: BackgroundDome-type carcinoma (DC) is a distinct variant of colorectal adenocarcinoma and less than 10 cases have been described in the literature. Most of the previously reported cases were early lesions and no endoscopic observations have been described so far. We herein report a case of a DC invading the subserosal layer, including endoscopic findings.Case presentationA highly elevated lesion in the transverse colon was diagnosed by colonoscopy in a 77-year-old man. The tumor appeared to be similar to a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Most cases are reported in the early growth phase: eight over ten case reported are T1N0, [16] one is T2N0 [3], and the last one is T3N0 [7]. No recurrence is documented so far and the patient presented with this report is one-year recurrence-free.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Most cases are reported in the early growth phase: eight over ten case reported are T1N0, [16] one is T2N0 [3], and the last one is T3N0 [7]. No recurrence is documented so far and the patient presented with this report is one-year recurrence-free.…”
Section: Discussionmentioning
confidence: 84%
“…Since the initial reports back in late 90's & 2000's by De Petris et al [1] and Jass et al [2] 10 cases of dome-type (DC) adenocarcinoma of the colon have been reported [17]. DC is considered a rare variant of carcinoma of the colon presenting as a nonpolypoid plaque lesion, it is thought to derive from the specialized columnar M-cells of dome epithelium, which makes up in association with the gut-associated lymphoid tissue the domelike masses that bulge into the gut lumen [2].…”
Section: Introductionmentioning
confidence: 99%
“…GALT carcinoma and GALT-associated PEM share some overlapping histopathologic features, including submucosal localization, well defined round contour with expansive growth, absence of desmoplasia, cystically dilated glands, and close association with submucosal GALT [12,13]. Most cases of GALT carcinoma reported so far were confined to the submucosal layer; only two of 23 cases reported as GALT carcinoma showed tumor extension beyond the submucosa [13,16,19,24]. Some prefer to use the term "pseudoinvasion" over "epithelial misplacement," emphasizing the expansive lobular growth pattern of tumor glands located in the submucosa after herniation [41].…”
Section: Discussionmentioning
confidence: 99%
“…The following histologic features characteristic of GALT carcinoma were evaluated: oncocytic cytoplasm of submucosal glands and depletion of goblet cells in submucosal glands [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]47].…”
Section: Histopathologic Evaluationmentioning
confidence: 99%
“…Another similarity is that almost all tumors reported are early-invasive, limited to the submucosa (T1) except in cases of DC reported by Amussen in 2008 (T2) [ 2 ] and by Yamada in 2012 (T3) [ 8 ]. No metastases to lymph nodes or to distant sites are reported.…”
Section: Introductionmentioning
confidence: 88%